Investigation of the efficiency of powder activated carbon magnetized with Fe3O4 nanoparticles in the removal of catechol from aqueous solutions by response surface methodology - S Fallah Jokandan; M Yegane Badi; A Esrafili; A Azari; E Ahmadi; H Tarhandeh; M Kermani (سلامت و محیط, 2019)
Background and Objective: The activities of various industries produce a wide range of pollutants and toxic compounds. One of these compounds is the catechol, a cyclic organic compound with high toxicity and resistant to degradation. Therefore, the purpose of this study was to investigate efficiency of powder activated carbon magnetized with Fe3O4 nanoparticles in the removal of catechol from aqueous solutions by response surface methodology. Materials and Methods: The co-precipitation method was used to synthesize magnetic powder activated carbon and its properties were analyzed by SEM and XRD analysis. Then, the effect of the parameters such as pH, contact time, absorbent dose, initial concentration of catechol and temperature on the efficiency of adsorption process were investigated using a response surface methodology (Box–Behnken). The residual concentration of catechol was measured by HPLC at 275 nm. Results: The results showed that the maximum efficiency of the adsorption process was obtained at concentration of 20 mg/L, pH=3, contact time 90 minutes, at 25 °C and absorbent dose of 1.5 g/L. The study of isotherm and kinetics showed that the experimental data of the catechol adsorption process correlated with the Langmuir and pseudo-second order models, respectively. Thermodynamic study of the reaction also expresses the Exothermic and Spontaneous process. Conclusion: The results showed that the adsorption process using powder activated carbon magnetized with Fe3O4 nanoparticles at acidic pH had better efficiency. As a result, the studied process as an effective, rapid and inexpensive method for removal of catechol from aqueous solutions is proposed. Due to its short reaction time, it is economically affordable process.